More Positive Emotions During the COVID-19 Pandemic Are Associated With Better Resilience, Especially for Those Experiencing More Negative Emotions - Israelashvili, Jacob (Frontiers in Psychology, 2021)
The ongoing COVID-19 pandemic has taken a significant toll on mental health; people around the world are experiencing high levels of stress and deteriorated wellbeing. Past research shows that positive emotions can help people cultivate a resilient mindset, however the reality created by the global crisis itself limits the opportunities for experiencing positive emotions. Thus, it is unclear to what extent their effect is strong enough to counter the psychological impact of the current pandemic. Here we report the findings of a survey conducted across two large representative samples in the UK and US (N total =2000) during the first wave of the COVID-19 pandemic (in Spring 2020). A linear regression model revealed that the presence of positive emotions is strongly linked with resilience, in particular for individuals experiencing more negative emotions. These results show that positive emotions are particularly important to mental health in the context of high stress, reflected by increased levels of negative emotional experiences. We discuss the potential of positive emotions to transform suffering and thereby ameliorate the negative impact of the present collective crisis